Optimization Of Sustainability Report Disclosure In The Banking Sub Sector In Indonesia - Hasibuan, Zahara Aulia; Hapsari, Dini Wahjoe (UNIVERSITAS PAKUAN, 2024)
SR disclosure is a type of business action that entails notifying all stakeholders involved about an entity's performance in order to encourage sustainable growth. This paper examines how SR disclosure in the bank sectorlisted on thepIndonesiaxStock Exchange (IDX) between 2019 and 2021 is impacted by business size, foreign ownership, and independent boards of commissioners. Several disclosure results within the same sub-sector indicate that banks have not taken part in CSR efforts. Foreign ownership, foreign scale, and the use of an independent board of commissioners are all utilised as criteria to encourage the publishing of sustainability reports. In this study, 30 samples from the BEI listed bank sub sector from 2019 to 2021 were used. This studywuses panelpdata with cross-sectional and time-series data. Sustainability reports and annual reports were used to gather the data for this study, which was then processed and evaluated using statistical tools like Eviews 12. The research reveals that the only factors that affect SR disclosure are firm size, independent board of commissioners, and foreign ownership.